HOW TO ASSESS THE COMPETENCE OF MEDICAL STUDENTS? WHAT TO ASSESS? - V.G. Marichereda; A.P. Rogachevsky; M.M. Kashtalian; T.Ya. Moskalenko; N.M. Kashtalian (Проблеми екології та медицини)
Trends in higher education will require from lecturers to take a new look at the ways of assessing the competencies acquired by the student. International trends in education have shifted from the traditional method of assessment (that is, the approach with the lecturer in the spotlight) to the modern one (that is, the student-centered approach). The student-centered method of assessment focuses more on what is expected from students in terms of skills at the end of the course, and the teaching process itself is not strictly regulated. Thus, today we face a transition period in higher education, when there is a problem of combining passive teaching methods with an attempt to assess the results of active learning. To solve the problem and to overcome the transition period as soon as possible, it is necessary to clearly define the notion of an “educational goal”. The concept of competence includes not only the cognitive and operational-technological component, but also the motivational, ethical, social and behavioral. It also includes the results of learning (for example, the ability to solve clinical problems), a value orientation system and skills. “Assessment” is a broad term that includes quantitative assessment, qualitative assessment and testing. Understanding the links between these concepts is important for lecturers in order to be able to distinguish them and to use them correctly in planning and teaching their courses. Assessment is critical to effective teaching. It is important that assessment is carried out permanently and continuously during the knowledge teaching and learning. Thus, it would provide information about the level of students’ understanding. It is also important to plan assessments so that students can monitor their learning strategy and apply the acquired knowledge and skills in practice.